Morfologia do esqueleto apendicular e das cinturas peitoral e pélvica dos Titanosauridae (Dinosauria: Sauropoda) do neocratáceo de Minas Gerais, Brasil - Trotta, Marcelo Newton Ferreira (2002)
Seventy-two appendicular and girdle bones referred to the family Titanosauridae (Dinosauria: Sauropoda) are described and figured. They have been found in Continental Upper Cretaceous strata of Brazil (Bauru Basin), near the city of Peirópolis, state of Minas Gerais. All of them were collected, together with vertebrae and three pelves, from 1947 to 1974 by L. I. Price, who passed away before he could study them. The material comes from three main sites: "Site 1 or Caieira", "Rodovia", and "Serra da Galga". The bones which are not referable to any of these sites, or are isolated findings, have been scored as Peirópolis surroundings". The study detected morphological variation in most of the bone categories, which were separated into 1 ( coracoid, humerus, tibia), 2 (scapula., sternal plate, ulna, femur, fibula), 3 (pubis, ischium) or 4 (radius) distinct morphotypes. The morphotypes are widespread among the three main collecting sites. From a total of 42 possible synapomorphies described in the literature, which are related exclusively to girdle and limb bones, 33 are present in the Peirópolis material. The presence of these synapomorphies diagnose this material as Sauropoda, Titanosauria, Titanosauridae (non-Saltasaurinae). The bones from Peirópolis were preliminary compared with other titanosaurid species of the world, especially from Argentina. They show both similar and unique morphological features in respect to other titanosaurid species.